2016
DOI: 10.1016/j.jtcvs.2015.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of “high-risk” donor hearts: Implications for infection

Abstract: We present the only single-center series on recipients of heart transplants from HRD CDCs. This potential source of suitable donor organs is shown to lead to excellent survival, without an increased incidence of perioperative or postoperative complications. Furthermore, the risk of transmission of infection from donors in this subgroup seems to be minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…These findings are similar to the adult study evaluating outcomes of blood culture positive donors in kidney, liver, and heart transplantation . Selective use of PHS “increased risk” donors has been shown in other analysis to result in similar post‐transplant survival . Donors at high risk of positive blood culture or those with known positive blood culture likely comprise some of this “increased risk” pool for which post‐transplant survival is not impacted and therefore if all else with the donor seems suitable for transplant (considering the candidate's risk profile) then donor should not be declined solely on the basis of positive blood culture or likely positive blood culture.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These findings are similar to the adult study evaluating outcomes of blood culture positive donors in kidney, liver, and heart transplantation . Selective use of PHS “increased risk” donors has been shown in other analysis to result in similar post‐transplant survival . Donors at high risk of positive blood culture or those with known positive blood culture likely comprise some of this “increased risk” pool for which post‐transplant survival is not impacted and therefore if all else with the donor seems suitable for transplant (considering the candidate's risk profile) then donor should not be declined solely on the basis of positive blood culture or likely positive blood culture.…”
Section: Discussionsupporting
confidence: 73%
“…20 Selective use of PHS "increased risk" donors has been shown in other analysis to result in similar post-transplant survival. 10 Donors at high risk of positive blood culture or those with known positive blood culture likely comprise some of this "increased risk" pool for which post-transplant survival is not impacted and therefore if all else with [43][44][45][46] The use of BCPD, along with active surveillance and judicious use of antibiotics in such recipients, will allow an expansion of the donor pool for pediatric heart transplant recipients without increasing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings were supported by that of Patel et al who found no negative impact on recipient survival after transplant with an HCV donor heart provided they had pre‐screening. On the contrary, Xu et al’s findings described an increased risk of transmission of hepatitis C positivity as well as hepatitis B positivity between the IRD and recipient. We report similar findings as described in the study by Xu et al where HCV seropositivity was significantly associated with worse survival.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown no difference in survival and post-operative outcomes between patients who received IRD grafts or SRD grafts. [1][2][3][4][5][6] There are scant data in literature assessing the impact of individual risk factors of these IRDs on recipient outcomes. The present study aims to investigate the association between the social behaviors of IRD and recipient outcomes after heart transplantation.…”
Section: Introductionmentioning
confidence: 99%